Manufacturing hydrophobic surfaces on aluminium substrates by micro-milling with end-ball nose tools - Guerrero-Vacas, Guillermo; Fusco, Schon; Rodríguez-Valverde, Miguel Ángel; Rodríguez-Alabanda, Oscar (Journal of manufacturing processes, 2024)
In industrial sectors such as automotive, aeronautics or medical, among others, anticorrosive, antibacterial, self-cleaning, and anti-sticking surfaces are demanded. Thus, the production of these surfaces by scalable processes is currently a subject of intense research but the processes are often complex, slow and use expensive and harmful chemical reagents. In this work, the micro-milling technique with ball nose tools has been proposed as a scalable and environmentally friendly way to improve water repellency on surfaces processed in a 5000 series aluminium and then treated with a hydrophobic coating. Thus, a novel arch-pyramidal protrusion-based surface texture generated by milling has been optimized by means of an experimental set up according to Taguchi's method, evaluating the influence of the process variables on surface hysteresis and hydrophobic capacity of the processed surfaces by means of static, sliding, advancement and receding angle measurements. Classical wettability models have made it possible to define hydrophobic specimens and the appropriate relationships between the water droplet size (d) and the radial milling step (p) have been identified to obtain the better hydrophobic behaviour. So, textures with lower values of crest height (h) and lower roughness factor (r) have shown better hydrophobicity for bigger water droplets of 50–100 μl and when the ratio d/p is higher. After undergoing over 60 cycles of a peel wear test standardized according to ASTM D 3359-09, the micromilled hydrophobic surfaces exhibit sustained hydrophobic properties, with sliding angles slightly increasing but stabilizing around 11°, indicative of preserved hydrophobicity. [Display omitted]